Exact Modeling of Binary Decision Diagram Complexity - Raseen, Mohamed; Venitha, E (International Journal of Engineering and Technology, 2018)
An exact model of Binary Decision Diagram (BDD) complexity is derived in this paper. An estimate of BDD complexity using models has already been proposed. The estimated BDD complexity in previous papers is just an approximation of experimental data using a curve that fits the data. Mathematical analysis indicates that many curves can be fitted to the same data. This paper derives the exact model for the BDD complexity by analysis. In order to derive the exact model, relation between the SOP (Sum Of Product) terms and Min-terms was analyzed. Further the variation of BDD size for various Min-terms was also analyzed. Finally the plot between the experimental BDD size and the derived exact model proves the accuracy of the derived model.Â Â